Hubungan Asupan Magnesium dan Rasio Lingkar Pinggang Panggul (RLPP) dengan Kejadian Dismenore pada Remaja Putri di Kecamatan Tambakboyo - Susinta Melida; Dian Ayu Ainun Nafies (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Dysmenorrhea remains a common health problem among adolescent girls and may interfere with their daily activities. This condition is not only associated with hormonal factors but is also influenced by dietary intake patterns and body fat distribution. This study employed an analytical observational design with a cross-sectional approach involving 207 adolescent girls selected using a stratified random sampling technique. Data collection was conducted using several instruments, including a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess magnesium intake, waist-to-hip ratio (WHR/RLPP) measurements using a measuring tape, and menstrual pain intensity assessed using a pain scale. The relationships between variables were analyzed using the Spearman correlation test with a significance level of p < 0.05. The results showed that magnesium intake demonstrated a significant inverse relationship with pain intensity, indicating that higher magnesium intake was associated with lower menstrual pain levels. In addition, WHR was also significantly associated with dysmenorrhea among adolescent girls. Overall, it can be concluded that magnesium intake and WHR are related to the occurrence of dysmenorrhea.